Design and Development of Ta’bir Teaching Materials to Improve Students’ Speaking Ability Based on Arabic Literature/ Desain dan Pengembangan Bahan Ajar Ta’bir untuk Meningkatkan Kemampuan Berbicara Peserta Didik Berbasis Sastra Arab - Hula, Ibnu Rawandhy N.; Alhasni, Aminah (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
This study aims to design and develop Arabic literature-based teaching materials that can effectively improve students' speaking skills. The method used is Research and Development (R&D) with the 4-D model (Define, Design, Develop, Disseminate), applied to 60 ninth-grade students at MTs Alkhairaat Gorontalo. Validation results from language experts, content experts, and media experts indicate that the module has excellent quality and is suitable for use. The implementation of the teaching materials showed a significant improvement in students' speaking skills, with an average pretest score of 57.68 increasing to 75.83 on the posttest (p < 0.05), and an average gain score of 0.44, which falls into the moderate category. Student responses through questionnaires also indicated high levels of satisfaction with the clarity, relevance, and effectiveness of the teaching materials. This study contributes to enriching the approach to Arabic language learning by integrating literature as an educational medium that strengthens linguistic and cultural aspects. These findings open opportunities for the development of more interactive, contextual, and humanistic value-based teaching materials. Further research is recommended to test the effectiveness of these teaching materials on other language skills and in the context of digital learning.Penelitian ini bertujuan untuk mendesain dan mengembangkan bahan ajar ta'bir berbasis sastra Arab yang mampu meningkatkan kemampuan berbicara siswa secara efektif. Metode yang digunakan adalah Research and Development (R&D) dengan model 4-D (Define, Design, Develop, Disseminate), yang diterapkan pada 60 siswa kelas IX di MTs Alkhairaat Gorontalo. Hasil validasi dari ahli bahasa, materi, dan media menunjukkan bahwa modul memiliki kualitas sangat baik dan layak digunakan. Penerapan bahan ajar menunjukkan adanya peningkatan signifikan dalam kemampuan berbicara siswa, dengan rata-rata skor pretest 57,68 meningkat menjadi 75,83 pada posttest (p < 0,05), dan rata-rata gain score sebesar 0,44 yang termasuk kategori sedang. Respon siswa melalui angket juga menunjukkan tingkat kepuasan tinggi terhadap kejelasan, relevansi, dan keefektifan bahan ajar. Penelitian ini berkontribusi dalam memperkaya pendekatan pembelajaran bahasa Arab dengan mengintegrasikan sastra sebagai media edukatif yang memperkuat aspek linguistik dan budaya. Temuan ini membuka peluang bagi pengembangan bahan ajar yang lebih interaktif, kontekstual, dan berbasis nilai-nilai humanistik. Penelitian lanjutan disarankan untuk menguji efektivitas bahan ajar ini pada keterampilan bahasa lainnya serta dalam konteks pembelajaran digital.